Amniotic Fluid Ischemia Modified Albumin as a Novel Prenatal Diagnostic Marker for Down Syndrome: A Prospective Case-Control Study - Guven, Suleyman; Comert, Erhan Huseyin; Guven, Emine Seda Guvendag; Demir, Bulent; Karcaaltincaba, Deniz (Clinical Journal of Obstetrics and Gynecology, 2023)
Aims: There is no study in the literature about ischemia-modified albumin (IMA) and hepatocyte growth factor (HGF) levels in amniotic fluid for Down syndrome cases. The aim of this study was to investigate the changes of IMA and HGF in Down syndrome cases at 16-20 weeks of gestation compared to normal fetuses. Methods: For this prospective case-control study, following reaching the number of 20 women (study group) who had the prenatal diagnosis of Down syndrome, maternal and gestational age-matched pregnant women with normal constitutional karyotype were selected for the control group (n = 74) from the stored amniotic fluid samples. Results: Mean women and gestational ages were comparable between the two groups. Amniotic fluid IMA (1.32 ± 0.13 vs. 1.11 ± 0.11 ABSU, respectively, p < 0.001) and HGF (2743.53 ± 1389.28 vs. 2160.12 ± 654.63 pg/mL, respectively, p = 0.008). Levels were significantly higher in pregnant women having Down syndrome fetuses compared with women having normal fetuses. The amniotic fluid IMA levels for the diagnosis of Down syndrome, and the sensitivity and specificity were calculated as 95.0% and 71.6% for the limit value 1.171 cm3, respectively. Conclusion: In cases with suspected Down syndrome, the diagnosis of Down Syndrome may be made in approximately 1 hour with high sensitivity and specificity by measuring the IMA level in the amniotic fluid sample taken for fetal karyotyping.